Bipolar disorders - Vieta, Eduard; Berk, Michael; Schulze, Thomas G.; Carvalho, André F.; Suppes, Trisha; Calabrese, Joseph R.; Gao, Keming; Miskowiak, Kamilla W.; Grande, Iria (Nature reviews. Disease Primers, 2018)
Bipolar disorders are characterized by acute episodes of mania or hypomania and depression. Psychosis can occur in some patients, and cognitive symptoms, including deficits in executive function and memory, are frequent. In this Primer, Vieta et al. discuss the epidemiology, mechanisms, diagnosis and management of bipolar disorders.
Gesehen am 21.04.2020